STRATEGI KOMUNIKASI POLITIK PEREMPUAN DALAM MERAIH KEPEMIMPINAN DAERAH - Sa’diyah El Adawiyah; Aida Vitayala Hubeis; titik Sumarti; Djoko Susanto (Metacommunication: Journal of Communication Studies, 2019)
ABSTRACT                 Direct elections open opportunities for various layers of society, especially women, to color the direction of local democracy. The presence of women as regional heads is one strategy for the birth of a more gender-equitable policy. The efforts of women to achieve political leadership in the regions are not easy. Many factors influence women in gaining regional leadership. Therefore it is important and relevant to examine how the political communication process that women build in achieving regional leadership. The aim of the study was to identify and analyze the role of regional leaders as political communicators in local politics, and to identify the media and political communication channels used by regional leaders in gaining regional leadership. In addition, it is to formulate a political communication strategy for regional leaders in gaining regional leadership. The methodology of this study uses qualitative phenomenological approaches. The results showed that the role of regional leaders as political communicators in local politics had a lot to color the local political map, both at the provincial and district / city levels, although it was not proportional to the total number of regional heads and mandates of existing regulations. The communication channel or media commonly used by female regional leaders in this study is to use a communication and group communication approach, both directly through face-to-face meetings and through digital social media currently available. The use of the media channel was felt effective in introducing themselves, increasing the popularity and electability of female leaders in the area. The political communication strategy of women leaders in reaching regional leadership has three stages, namely networking strategies, message packaging strategies and media determination strategies.Keywords: female leaders, political communication, media channels, communication strategies ABSTRAK Pilkada langsung membuka peluang pada berbagai lapisan masyarakat terutama kaum perempuan untuk ikut mewarnai arah demokrasi lokal. Kehadiran perempuan sebagai kepala daerah merupakan salah satu strategi bagi lahirnya kebijakan yang lebih adil gender. Upaya perempuan dalam meraih kepemimpinan politik di daerah bukanlah hal yang mudah. Banyak faktor yang memengaruhi perempuan dalam meraih kepemimpinan daerah. Oleh karena itu menjadi penting dan relevan untuk mengkaji bagaimana proses komunikasi politik yang dibangun perempuan dalam meraih kepemimpinan daerah. Tujuan penelitian adalah mengidentifikasi dan menganalisis peranan perempuan pemimpin daerah sebagai komunikator politik dalam politik lokal, serta mengidentifikasi media dan saluran komunikasi politik yang digunakan perempuan pemimpin daerah dalam meraih kepemimpinan daerah. Selain itu adalah merumuskan strategi komunikasi politik perempuan pemimpin daerah dalam meraih kepemimpinan daerah. Metodologi penelitian ini menggunakan kualitatif dengan pendekatan fenomenologi. Hasil penelitian menunjukkan bahwa peranan perempuan pemimpin daerah sebagai komunikator politik dalam politik lokal telah banyak mewarnai peta politik lokal, baik di tingkat provinsi maupun kabupaten/kota, walaupun belum proporsional dengan jumlah keseluruhan kepala daerah dan amanat dari regulasi yang telah ada.  Saluran komunikasi atau media yang umum digunakan oleh pemimpin daerah perempuan dalam penelitian ini adalah dengan menggunakan pendekatan komunikasi dan juga komunikasi kelompok, baik secara langsung melalui pertemuan tatap muka dan melalui media sosial digital yang ada saat ini.  Pemanfaatan saluran media tersebut dirasakan efektif untuk memperkenalkan diri, meningkatkan popularitas dan elektabilitas dari tokoh perempuan pemimpinan daerah tersebut. Strategi komunikasi politik perempuan pemimpin daerah dalam meraih kepemimpinan daerah memiliki tiga tahapan, yaitu strategi membangun jejaring, strategi pengemasan pesan dan strategi penentuan media.Kata Kunci: Pemimpin perempuan, komunikasi politik, saluran media, strategi komunikasi dan daerah